Review of the subgenus Scatella Robineau-Desvoidy, 1830 from China (Diptera: Ephydridae) - Zhang, Junhua; Yang, Ding (Zootaxa, 2005)
The species of the subgenus Scatella Robineau-Desvoidy from China are reviewed. One species, Scatella tenuicosta Collin, is recorded from China for the first time, and one species, Scatella henanensis sp. nov., is described. A key to the species from China is given. The distribution of the subgenus in China is discussed.